DEPRESSIVE SYMPTOMS AMONG OLDER ADULTS AND ASSOCIATED FACTOR IN HANOI IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence of depressive symptoms and identify associated factors among older adults in Hanoi in 2025.Methods: A cross-sectional study was conducted from July 2024 to June 2025 on 265 older adults living in Thinh Quang Ward (Dong Da District) and Cua Nam Ward (Hoan Kiem District), Hanoi. Multivariate logistic regression model was performed to identify associated factors with depressive symptoms.  Results: The prevalence of depressive symptoms among older adults was 20.4% (GDS score > 5 out of a maximum of 15 points), increasing with age and reaching the highest rate among those aged ≥80 years. Several determinants were associated with depressive symptoms. Those who were unemployed (aOR = 3.4; 95%CI: 1.03–11.29), diagnosed with comorbidity, including having 1 chronic disease (aOR = 6.2; 95%CI: 1.51–25.59), 2 diseases (aOR = 4.1; 95%CI: 1.12–15.01), 3 or more diseases (aOR = 4.9; 95%CI: 1.08–22.01), and those who experienced difficulties in basic activities of daily living (aOR = 6.2; 95%CI: 2.33–16.52) were more likely to suffer from depressive symptoms than their counterpart. Those who actively engaged in social activities (i.e. social interaction (aOR = 0.3; 95%CI: 0.09–0.96), helping others (aOR = 0.2; 95%CI: 0.04–0.67), were less likely to have depressive symptoms.Conclusion: Approximately 20.4% of study participants had depression symptoms. Future healthcare and social care programs for older adults should focus on promoting social engagement at levels of “social interaction” and “helping others”, managing chronic diseases, and supporting older adults in performing daily activities. Moreover, promoting income-generated opportunities for older adults is essential for maintaining their economically independence.
Keywords: depressive symptom, older people, social participation.